Deciphering the Structure-Property Relations in Substituted Heptamethine Cyanines - Štacková, Lenka; Muchová, Eva; Russo, Marina; Slavíček, Petr; Štacko, Peter; Klán, Petr (The Journal of organic chemistry, 2020)
Heptamethine cyanines (Cy7) are fluorophores essential for modern bioimaging techniques and chemistry. Here, we systematically evaluated the photochemical and photophysical properties of a library of Cy7 derivatives containing diverse substituents in different positions of the heptamethine chain. A single substitution allows modulation of their absorption maxima in the range of 693-805 nm and photophysical properties, such as quantum yields of singlet-oxygen formation, decomposition, and fluorescence or affinity to singlet oxygen, within 2-3 orders of magnitude. The same substituent in different positions of the chain often exhibits distinctly contradictory effects, demonstrating that both the type and position of the substituent are pivotal for the design of Cy7-based applications. The combination of experimental results with quantum-chemical calculations provides insights into the structure-property relationship, the elucidation of which will accelerate the development of cyanines with properties tailored for specific applications, such as fluorescent probes and sensors, photouncaging, photodynamic therapy, or singlet-oxygen detection.